The effects of poling on energy consumption, kinematics and kinetics in roller ski skating - Grasaas, E. (2013)
The current study investigated the effect of poling on physiological, kinematic and kinetic responses at different velocities by comparing the G4 skating technique with (G4-P) and without (G4-NP) poling. The G4 involves a "strong side" with poling action and a "weak side" with arm swing. 17 elite male cross-country skiers performed 4-min submaximal tests at 10, 15 and 20 km ·h-1 on a 2% inclined treadmill using G4-P and G4-NP. Physiological, kinematic and kinetic variables were assed with open- circuit indirect calorimetry, blood lactate analysis, Qualisys Pro Reflex system and roller skis integrated with two full bridged strain gauges. Gross efficiency (GE) was calculated by the external work rate against friction and gravity divided by the metabolic rate in aerobic steady state conditions. O2 consumption, ventilation and blood lactate concentration were lower with G4-P than G4-NP at all velocities and thus, GE was higher in the two examined velocities with G4-P compared to G4-NP (11,1% vs 9,9%; 12,5% vs 10,6%; all P < 0.05). Longer cycle lengths at lower cycle rates, as well as less ski angling and edging were demonstrated with G4-P compared to G4-NP from low to high velocities, with a 15% difference in cycle length at high velocity (all P < 0.05). Force impulse was lower with G4-P compared to G4-NP for the "strong side" at low and high velocity (both P < 0.05). Rate of force development and peak force were lower for both strong and weak sides with G4-P compared to G4-NP, and the ski velocity was on average higher on the strong side for G4-P at all velocities (all P < 0.05). Altogether, these results demonstrated lower physiological demands and higher gross efficiency at a given work rate when elite skiers added poling to the G4 skating technique. At the same time, skiers increased their cycle lengths and showed significant changes in the cycle characteristics by increasing the ski velocity and reducing the applied ski forces of both the strong and weak sides when poling.